2021
DOI: 10.1016/j.ijid.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Variations in rifampicin and isoniazid resistance associated genetic mutations among drug naïve and recurrence cases of pulmonary tuberculosis

Abstract: Background: The resistance to first-line drugs can increase the risk of treatment failure and development of resistance to other anti-TB drugs. In TB endemic settings, a considerable rate of recurrence cases exhibited each, year which adds significant burden to the prevalence of disease worldwide. Methods: A total of 562 sputum samples were collected from presumptive positive clinical cases of MDR tuberculosis. Treatment history and demographic data of the patients were obtained after informed consent. Xpert M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Our results are in line with previous studies conducted in Ethiopia, which also found no isolates with combined mutations in both katG and inhA genes 7 , 31 , 34 or triple mutations at the rpoB , katG , and inhA genes from India. 9 By contrast, other studies have shown a higher rate of double mutations at both the katG and inhA genes of INH-mono-resistant isolates in the Central Africa Republic (4.2%), 36 China (13.4%) 11 and (3.4%), 12 Pakistan (14.7%) 40 and (1.1%), 32 South Africa (22.7%), 41 Burkina Faso (14.5%), 33 and India (3.4%). 9 The extent of INH resistance conferred by various mutations may vary depending on the genetic background of the strain.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results are in line with previous studies conducted in Ethiopia, which also found no isolates with combined mutations in both katG and inhA genes 7 , 31 , 34 or triple mutations at the rpoB , katG , and inhA genes from India. 9 By contrast, other studies have shown a higher rate of double mutations at both the katG and inhA genes of INH-mono-resistant isolates in the Central Africa Republic (4.2%), 36 China (13.4%) 11 and (3.4%), 12 Pakistan (14.7%) 40 and (1.1%), 32 South Africa (22.7%), 41 Burkina Faso (14.5%), 33 and India (3.4%). 9 The extent of INH resistance conferred by various mutations may vary depending on the genetic background of the strain.…”
Section: Discussionmentioning
confidence: 85%
“… 37 By contrast, the frequency of mutation at codon S450L in our study was higher than the previous report from Iran (40%) 38 and China (31.25%) 39 but lower than studies conducted in the Tigray region of Ethiopia (70%), 31 Addis Ababa Ethiopia (81.3%), 30 and Pakistan (85%). 40 The high-frequency occurrence of the S450L mutation in the rpoB gene associated with RIF resistance may indicate that drug resistance has been acquired, resulting in a reduced fitness cost. The possible reasons for the differences in the occurrence of specific mutations in the rpoB gene could be due to the patterns of drug resistance-conferring mutations, geographic locations, and sociodemographic characteristics of the study participants, including HIV co-infection and prior TB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…With the ongoing COVID-19 pandemic now overwhelming health services, patient compliance for both newly diagnosed and recurrent PTB cases may be affected. Retreated cases are at more risk of developing hot spot Mtb mutations and increased risk of resistance with poor treatment outcome (Allwood et al, 2021;Kabir et al, 2020). Thus a rise in numbers of cases of MDR-TB or RPTB could be predicted in light of this.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the surgical intervention accompanied by indispensable anti-tubercular drug therapy is the primary routine treatment ( Mukewar et al, 2012 ; Shrivastava et al, 2019 ; Moosa et al, 2020 ; Phillips et al, 2020 ). Although rifampicin (RIF) and isoniazid have been widely chosen as clinical anti-tubercular drugs due to their excellent effectiveness and reasonable price ( Hakkimane et al, 2018 ; Campbell et al, 2020 ; Sterling et al, 2020 ; Villa et al, 2020 ; Kabir et al, 2021 ), their short plasma life and relatively low concentration in tuberculosis granulomas and the inescapable side effects of chemotherapeutic drugs have drawn growing attention from interdisciplinary and clinical medicine research circles ( Du Toit et al, 2006 ; Dartois, 2014 ; Liao et al, 2020 ). Thus, there is an urgent need to develop an efficient chemotherapy strategy for tuberculosis.…”
Section: Introductionmentioning
confidence: 99%